Dampak Kejadian La NiÃ±a Terhadap Curah Hujan Di Kabupaten Jembrana - Baiq Helmi Susrinda; Wahyu Widodo Putranto (Universitas Hamzanwadi, 2019)
Rainfall variability in Indonesia could be affected by global phenomenon like La NiÃ±a by looking at the intensity value of Southern Oscillation Index (SOI) and anomaly value of SPL. The amount of these effect varies from one place to another. Jembrana Regency is one of the Regency of Bali Province. Jembrana Regency is located at 8°09'30